Mechano-energetic efficiency in patients with hypertrophic cardiomyopathy with and without sarcomeric mutations. (3rd October 2022) - Borrelli, F; Lombardi, R; Canciello, G; Frisso, G; Todde, G; Paoletta, D; Esposito, G; Losi, M A
Abstract: Background: Hypertrophic Cardiomyopathy (HCM) is mainly caused by sarcomeric mutations. In about 40% of cases the causal mutation is unknown. Myocardial mechano-energetic efficiency per unit of left ventricular (LV) mass (MEEi) is an echocardiographic parameter of LV pump performance. Sarcomeric mutations may affect energy efficiency. Purpose: We investigated the effects of the presence of sarcomeric mutations on MEEi in patients with HCM. Methods: We included 49 genetically screened HCM patients (50±10 years, 27% women) with LV ejection fraction >50%, LV maximal wall thickness >14 mm and no moderate to severe mitral regurgitation. MEEi was calculated as the ratio between stroke volume and heart rate, normalized by LV mass. Echo-LV mass was calculated as LV epicardial minus LV endocardial volumes in 4 and 2 chamber views multiplied by 1.05, a method validated with nuclear magnetic resonance. Results: 27 HCM patients carried a sarcomeric mutation (HCM-Sarc; 55%). As shown in the table, patients with and without sarcomeric mutations (HCM-Sarc vs HCM-NoSarc) had similar LV ejection fraction, heart rate, LV mass and LV outflow tract gradient. HCM-Sarc showed early age at diagnosis, higher frequency of HCM family history and significantly reduced MEEi as compared with HCM-NoSarc. Presence of sarcomeric mutation could be predicted by younger age, lower MEEi and by family history of HCM (overall p<0.05). Conclusions: In a population of HCM patients, the presence of a sarcomeric mutation is the only determinant of reduced the LV pump performance as estimated by MEEi. MEEi may be used as an imaging biomarker in sarcomeric mutation carriers. Funding Acknowledgement: Type of funding sources: None.